Komodifikasi Budaya Musik Sampeq Kenyah - Bayu Arsiadhi Putra; Aris Setyoko (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
Abstract: The Dayak people of East Kalimantan have long been involved in the world of tourism. There is a cultural village in Samarinda called Pampang, mostly inhabited by the Dayak Kenyah community. In many ways, the government 'takes care of' the development of the Kenyah Pampang community, including its culture and music. It can indicate the government's concern for marginalized groups. However, at the same time, images of 'original', 'exotic' and 'primitive' cultures are being constructed to fit into commodified 'goods'. This view does affect not only the Dayaks themselves but also the government, tourists and private institutions involved in it. This paper aims to discuss how the history of the commodification of Kenyah's musical culture. The research method used is descriptive qualitative with a historical approach. The study results show that the development of the Kenyah Pampang community's musical culture cannot be separated from the commodification brought in by the tourism body. The commodification of Dayak Kenyah's music culture has changed relations among the people, increasing competition and suspicion, both intra and between ethnic groups. Often commodification is carried out with ideology, as in an effort to 'purify tradition'. Abstrak: Masyarakat Dayak di Kalimantan Timur telah lama mengambil bagian dalam dunia pariwisata. Terdapat sebuah desa budaya di Samarinda bernama Pampang, yang sebagian besar dihuni oleh masyarakat Dayak Kenyah. Dalam banyak hal pemerintah ‘mengurus’ pembangunan masyarakat Kenyah Pampang, termasuk budaya dan musiknya. Hal ini dapat menandakan kepedulian pemerintah terhadap kelompok marjinal. Namun saat bersamaan, imaji-imaji tentang kebudayaan ‘asli’, ‘eksotis’ dan ‘primitif’ sedang didikonstruksi agar layak menjadi ‘barang’ komodifikasi. Pandangan ini tidak hanya mempengaruhi Orang Dayak Sendiri tetapi juga pemerintah, wisatawan dan lembaga swasta yang terlibat di dalamnya. Tujuan penulisan ini adalah untuk membahas bagaimana sejarah komodifikasi budaya musik sampeq Kenyah. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan sejarah. Hasil penelitian menunjukkan perkembangan budaya musik masyarakat Kenyah Pampang tidak lepas dari komodifikasi yang dibawa dalam tubuh Pariwisata. Komodifikasi budaya musik Dayak Kenyah telah mengubah relasi di antara masyarakat, meningkatkan persaingan dan kecurigaan, baik intra maupun antar etnis. Seringkali komodifikasi dijalankan dengan ideologi, seperti dalam upaya ‘memurnikan tradisi’.